CRAFT: Comprehensive Resilience Assessment Framework for Transportation Systems in Urban Areas. (October 2020) - Koc, Eyuphan; Cetiner, Barbaros; Rose, Adam; Soibelman, Lucio; Taciroglu, Ertugrul; Wei, Dan
Abstract: Urban areas in the US and around the globe are facing increasingly complex resilience challenges. Among the components of the "urban system, " transportation networks are among the most critical facilitators that support the lives, interactions, and dynamics of urban dwellers. They are essential to the well-being of the society not only under business-as-usual conditions, but also during times of disaster for the entire response and recovery timeline. This paper introduces CRAFT (Comprehensive Resilience Assessment Framework for Transportation Systems in Urban Areas), which is designed to achieve holistic analyses of transportation disruptions by addressing the many shortcomings and research gaps in this domain. The framework couples a novel structure-specific modeling methodology with a high-fidelity metropolis-scale travel demand model based on real socioeconomic data, and produces results, which, in turn, serve as input for a state-of-the-art socioeconomic impact analysis methodology that is based on computable general equilibrium (CGE) analysis. By the virtues of its data-intensive, model-based, and cross-disciplinary nature, CRAFT aims to capture and incorporate many details that are usually neglected in traditional approaches, and generates resilience insights at 3 levels: (1) system component level (e.g., damages to bridges, tunnels and information on component recovery), (2) system level (e.g., road network disruptions, reconfiguration of traffic and network level functionality) and (3) regional economic level (e.g., impacts on regional GDP, employment, economic resilience). The objective of this paper is to introduce CRAFT and to demonstrate the workings of its first coupling between the hazard and transportation modules through a case study on the Greater Los Angeles Area.